Religious Movements in Humanitarian Issue: The Emergence of Faith-Based Organizations (FBO) in Diplomacy Sphere - Munthe, Fredy (Jurnal Hubungan Internasional, 2016)
Faith-Based Organization (FBO) has a strong role in conducting humanitarian Diplomacy. However, the strong role of nation-state in that sphere ignored the emergence of FBO. Until now, there is no text that explicitly discuses the emergence of FBO in humanitarian diplomacy. All of text only discusses the issue FBO and humanitarian action. In fact, there is no humanitarian aid if there is no humanitarian diplomacy previously. Therefore, this paper traces the emergence of FBO as the actor of humanitarian diplomacy. This paper analyzes the perspective of diplomacy and the impact to the emergence of FBO as the actor. I use literature review to get data about it. This paper is useful for strengthen position of FBO as the non-state actor in humanitarian sphere as well as in diplomacyÂ Organisasi berbasis agama (FBO) memiliki peran yang kuat dalam melakukan diplomasi kemanusiaan. Namun, kuatnya peran yang dimiliki negara-bangsa dalam lingkup diplomasi mengabaikan kemunculan FBO sebagai salah satu aktor. Sampai saat ini, belum ada teks yang secara eksplisit membahas munculnya FBO dalam diplomasi kemanusiaan. Semua teks hanya membahas masalah FBO dan aksi kemanusiaan. Namun faktanya, tidak ada bantuan kemanusiaan jika tidak ada diplomasi kemanusiaan sebelumnya. Oleh karena itu artikel ini mencoba untuk melacak munculnya FBO sebagai aktor diplomasi kemanusiaan. Artikel ini menganalisis perspektif diplomasi dan dampaknya terhadap kemunculan FBO sebagai aktor. Untuk melakukannya penulis menggunakan kajian literatur untuk mendapatkan data tentang hal tersebut. Artikel ini berguna untuk memperkuat posisi FBO sebagai salah satu aktor non-negara dalam ruang kemanusiaan begitu pula diplomasi